"Losing Your Land You Feel Like You're Losing Your Identity, Like You're Experiencing Slow Death": An Interview With Chief Thomas Dardar—Houma Nation. (November 2018) - Sullivan, John; Rosenberg, Beth
The Houma Nation was a major community hub for the Citizen Science Network seafood sampling conducted as part of the Gulf Coast Health Alliance: Health Risks Related to the Macondo Spill (GC-HARMS) research project. They also managed a clinical cohort to facilitate wellness checkups and collection of biological samples during the project. In this interview, Thomas Dardar, Principal Chief of the Houma Nation, outlines the historical and evolving changes—cultural as well as geophysical—that the Houma Nation must address in an uncharted era of climate-related impacts on weather patterns, sea levels, and sustainable land uses. He explores tribal efforts to cope with cumulative exposures, risks, and outcomes of industrial practices that have led to land loss and deterioration of natural marshlands. These changes challenge the perpetuation of traditional values based on multigenerational ties to their land base, and the bayous and estuarial waters they fish.